2010
DOI: 10.1186/1749-799x-5-16
|View full text |Cite
|
Sign up to set email alerts
|

Isolated thumb carpometacarpal joint dislocation: a case report and review of the literature

Abstract: BackgroundIsolated thumb carpometacarpal dislocation is a rare injury pattern and the optimal treatment option is still controversial.Case DescriptionWe present a 27-year-old basketball player who underwent an isolated dorsal dislocation of the thumb carpometacarpal joint after a fall. The dislocation was successfully reduced by closed means but the joint was found to be grossly unstable. Due to inherent instability, repair of the ruptured dorsoradial ligament and joint capsule was performed.The ligament was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 11 publications
0
35
0
2
Order By: Relevance
“…Fotiadis et al successfully repaired the ruptured dorsoradial ligament with suture anchors and repaired the joint capsule in an end-toend fashion in one patient with 3-year follow up. 22 The patient was pain free and returned to his previous level of activity. No restriction of carpometacarpal movements or residual instability was noticed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Fotiadis et al successfully repaired the ruptured dorsoradial ligament with suture anchors and repaired the joint capsule in an end-toend fashion in one patient with 3-year follow up. 22 The patient was pain free and returned to his previous level of activity. No restriction of carpometacarpal movements or residual instability was noticed.…”
Section: Discussionmentioning
confidence: 90%
“…An unpredictable outcome of conservative or minimally invasive methods was pointed out by Fotiadis et al in his case report, switching to repair of the ruptured dorsoradial ligament with j o u r n a l o f c l i n i c a l o r t h o p a e d i c s a n d t r a u m a 5 ( 2 0 1 4 ) 1 8 5 e1 9 2 suture anchor and joint capsule with fruitful result. 22 Simonian and Trumble compared early ligamentous reconstruction with closed reduction and pinning in two groups. 10 Their data in this retrospective study suggested that early open reduction and ligamentous reconstruction results in a better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal treatment strategy for traumatic Trapezio-metacarpal dislocation remains controversial. 2 Closed reduction and cast, open or closed reduction with temporary K-wire fixation, and dorsal capsule and ligament reconstruction have been used to stabilize the joint. However few cases have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Isolated dislocation of the CMC joint is uncommon and occurs in less than 1 % of all hand injuries [6,8]. It is more often combined with a fracture of the first metacarpal base [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…It is more often combined with a fracture of the first metacarpal base [7,9]. A pure dislocation of the CMC joint typically leads to a rupture of the DRL and POL [6][7][8]. Magnetic resonance (MR) imaging can be used to accurately evaluate these ligament injuries [5].…”
Section: Introductionmentioning
confidence: 99%